Cardiovascular outcomes in patients treated with sodium-glucose transport protein 2 inhibitors, a network meta-analysis of randomized trials - Tornyos, Dániel; Meuer, Maximilian; Lukács, Réka; El Alaoui El Abdallaoui, Oumaima; Kupó, Péter; Faludi, Réka; Komócsi, András (Frontiers in Cardiovascular Medicine, 2022)
Background Gliflozins altering the sodium-glucose transport protein 2 (SGLT2) in the nephron, represent alone or in combination a promising treatment option for patients with type II diabetes mellitus. In addition to glucose control, these drugs provide benefits including reduced risk of long-term cardiovascular (CV) and renal complications. Several trials evaluated gliflozins in patients with various degrees of cardiac dysfunction with heterogeneous results. Objectives We aimed to perform a comprehensive analysis of the effect of gliflozins on CV outcomes. Methods Systematic searches of electronic databases were conducted until September 2022. Multiple treatment network meta-analysis was performed in R. Random-effects model was used to combine risk estimates across trials calculating risk ratio (RR) with 95% confidence intervals as summary statistics. The primary endpoint of interest was the rate of heart failure-related hospitalization (HHF) and the composite of HHF with CV mortality (HHF+CVD). Secondary outcomes included major adverse cardiac events (MACE), CV- and overall mortality, myocardial infarction (MI), and stroke. Results Twenty-nine studies randomizing 88,418 patients were identified. Gliflozins reduced the risk of HHF (RR: 0.72 [0.69; 0.76]) and HHF+CVD (RR: 0.78 [0.75; 0.82]). The risk of MACE and its component also improved significantly except for stroke. The network analyses did not explore major differences among the individual substances. The only exception was sotagliflozin which appeared to be more effective regarding HHF+CVD, stroke, and MI compared to ertugliflozin, in HHF+CVD and stroke compared to dapagliflozin, and in stroke endpoint compared to empagliflozin. Conclusions Our meta-analysis supports a group effect of gliflozins beneficial in a wide spectrum of patients with a risk of HF development. In addition to the improvement of HF-related outcomes, the risk of major adverse events is also reduced with SGLT2 inhibition.